Pemanfaatan Beras Menir Menjadi Produk Bernilai Ekonomis pada UMKM di Desa Cimalaka - Mulyatillah, Waliah; Peliyanti, Manika Sunda; Regina, Winanti; Rachmaniar, Ananda (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2024)
One of the MSMEs in Cimalaka Village is Ikasari's MSMEs (Micro, Small and Medium Enterprises) which are engaged in food processing. In addition, Ikasari's also has private rice fields with abundant crops. The harvest will go through a post-harvest process which will eventually produce rice, and the rest of the rice milling results will become groin rice. The purpose of this activity is to utilize groat rice from rice milling into an economically valuable product for MSME owners in Cimalaka Village. The method used in this activity uses the PAR (Participatory Action Research) approach. The results of this activity have a positive impact and reduce crop waste to be more useful and add profits to Ikasari's MSMEs. The owner has done his own product marketing and sustainable product manufacturing.